Peak expiratory flow rate nomogram in relation to anthropometric determinants of South Indian school children - Abraham, Binu; Baburaj, Stephenson; Patil, Rahul Bhimrao; Mohandas, M K; Ruhman, Shibily; Raj, Sunil (Indian Journal of Child Health, 2014)
Background: The predictive normal value of peak expiratory flow rate (PEFR), used in monitoring of healthy and asthmatic children, is correlated with height, but it may vary with other anthropometric measurements and ethnic differences. Purpose: To study the correlation of PEFR with age, sex, body mass index (BMI), chest circumference (CC), and MUAC and to formulate PEFR nomograms in relation to these anthropometric variables in a rural school going children of age group 6-12 years in southern India. Methods: A descriptive cross-sectional study was conducted in 2000 children consist of 993 boys and 1007 girls who fulfilled the selection criteria from eight randomly selected government schools from a rural area. PEFR was measured age wise using Mini-Wright peak flow meter and the highest among the three values was taken. PEFR nomograms were formulated, and its correlation with BMI, height, weight, CC, and MUAC were estimated using linear regression analysis. Results: PEFR has strong (p < 0.001) positive correlation with age, height, weight, MUAC, and CC, but it has poor correlation with BMI (p = 0.985) which showed flat regression line with narrow 95% confidence limits. Conclusion: In this study, PEFR has nonsignificant correlation with BMI but has strong positive correlation with other anthropometric measurements. This underlines the need of a local reference nomogram as anthropometric measurements affect the PEFR reference values.